NILAI RELIGIUS PARIKAN BABADANA PADA TARI TOPENG LENGGER WONOSOBO - Felix Hansel Raditya Wibowo; Salsyabilla Adinda Putri (TAMUMATRA, 2026)
The Topeng Lengger Wonosobo Dance is a traditional art form that serves not only as entertainment but also contains strong religious values, particularly in the Parikan Babadana as the opening ritual in this performance. This study aims to analyze the religious values of Parikan Babadana in the Topeng Lengger Wonosobo Dance. This study uses a qualitative method with an ethnographic approach through observation, interviews, documentation, and discourse and semiotics analysis to interpret the lyrics of Parikan Babadana. The results show that Parikan Babadana contains spiritual exhortations to always remember God, reflections on transience, dependence, and prayers for safety. Thus, Parikan Babadana functions as a medium for the inculturation of religious values as well as a representation of the integration between Islamic teachings and Javanese culture. This study is expected to enrich the study of religious-based performing arts and support the preservation of spiritual meaning in traditional arts.